Scrub Typhus: Indian Situation and Current Report Generated by Indian Council of Medical Research-National Centre for Disease Informatics and Research under the Right to Information Act, 2005-reg - Rathor, Shivam (International Journal of Pharmaceutical & Biological Archive, 2024)
Scrub typhus infection in humans is caused by the obligatory, intracellular bacteria Orientia tsutsugamushi. This study explains the introductive part, historical background, epidemiology, pathogenesis, diagnosis, Indian situation of scrub typhus and the methodology of the Indian Council of Medical Research-National Centre for Disease Informatics and Research (ICMR-NCDIR). The results of this study show that there were 32355 incidents of scrub typhus overall in 2022 and 54162 cases overall in 2023. According to the report from ICMR-NCDIR under the Right to Information Act, 2005-reg, a total of 36 states in India were examined in the years 2022 and 2023; of those, 4 states did not report any cases of scrub typhus, and 32 states reported confirmed cases of the 32 states, 4 did not report any reports about scrub typhus in 2022, and in 2023, all 32 states reported confirmed cases of the disease.